Interview: Pasifika climate activist music in New Zealand, queered and disabled - Zemke, Kirsten; Leleiga Lim-Cowley, Luka (Perfect Beat, 2021)
This discussion is between Dr Kirsten Zemke, from the University of Auckland and her MA student-poet, dancer and climate activist, Luka Leleiga Lim-Cowley. Luka’s musical performance experiences in, and insights from, Pasifika climate activist and Pacific Indigenous sovereignty events led them to further explore the perspectives of Pasifika queer and/or disabled activists. Luka argues that disabled and gendersexuality-divergent folks should be at the foreground of these movements, as they are the most threatening to white supremacy—the ultimate culprit in Indigenous displacement and climate change. Luka’s poem, ‘Water (remix ii)’, is presented in full; the discussion flows through topics such as gender, religion, Indigeneity, and the continuums of time and space.